Determinacion del estado ecologico de la quebrada fruta del pan mediante la aplicacion de indicadores ambientales - Quevedo Alvarado, Anthony Vicente (2018)
The present study was carried out to determine the ecological status of a body of surface water located in the Parroquia Torata, Canton Santa Rosa, Province of El Oro. The Quebrada Fruta de Pan is the object of study, which is altered by the discharge of domestic wastewater, without timely treatment, affecting the quality of the water body reflected in the existing aquatic biodiversity. For the evaluation of the ecological status, 5 sampling points were established in which biological indexes were used, such as the BMWP index for macroinvertebrates, species deficit index for diagnosis, biological index of microphones in river for microphones, Jaccard similarity index for ichthyofauna. , and a physicochemical index to determine the level of contamination by organic matter (ICOMO); making use of the biological communities present in the different types of maps, based on the abundance of the species and identifying the representative species or indicator species, known for the sensitivity or tolerance to changes in the physical and chemical characteristics of the water, in addition to complemented with the physical analyzes of the body of water studied. The objective of the research was to determine the ecological state of the Broken Fruta de Pan, through the application of biological indexes and a physicochemical index, it was obtained as a result with the application of the biological indexes that points 1 and 2 are scarce. alteration in the indicators used, because there are no people living in these points to contribute waste to the stream, however, a bad ecological state was identified in points 3, 4 and 5, when it could be found regarding macroinvertebrates the family of families: Chironomidae and Culicidae, which can be found in waters with low oxygen content and high content of organic matter, where the larval stage, in addition to a small diversity of species that are also found in the whole of the ichthyofauna, microphytes and diatoms. In addition to the study of the biological communities, the water sample was taken for study in a laboratory on the following parameters: dissolved oxygen, total coliforms and the biochemical oxygen demand, using an index of contamination by organic matter, which reflects as well as the biological indicators the bad ecological state of the bankrupt in a 60% with respect to the points sampled in the sampled points 3, 4 and 5. In front of this problem a proposal is established that consists of the application of corrective measures for recover the ecological conditions that have been lost by the discharges of wastewater from the anaerobic upflow reactor (RAFA), due to its inefficient infrastructure and lack of maintenance, where it is sought to propose additional treatment systems proportional to the amount of wastewater that enters the aforementioned reactor, achieving the necessary of floating solids, settleable and in suspension, in addition to the total coliforms present in this type of water.